Use of short peripheral intravenous catheters: characteristics, management, and outcomes worldwide - Alexandrou, Evan; Ray-Barruel, Gillian; Carr, Peter J; Inwood, Shiela; Higgins, Nialls; Alberto, Laura; Mermel, Leonard; Rickard, Claire M; Daud, Azlina (Publication of the Society of Hospital Medicine, 2018)
BACKGROUND: Peripheral intravenous catheter (PIVC) use in health care is common worldwide. Failure of PIVCs is also common, resulting in premature removal and replacement.